G157(P) Changing Referral Patterns to a District Child Development Centre (CDC). (7th April 2014) - Fung, C; Mittal, R
Abstract : Background: The Court Committee (who originally described the CDC in 1976) suggested that the CDC's clinical role is to assess and investigate children's developmental delay, to give professional advice and support to parents and colleagues, to be available for consultation to field staff, and to provide a supporting service to special schools within the district. Despite CDC being in existence for nearly half a century, little is known of the profile of referrals. Aim: To analyse the referral patterns to the regional CDC of a district. Method: 470 children were referred to the CDT between September 2004 and July 2013 over a 9 year period. Data was obtained from record of initial referral, and retrospective data analysis was carried out. Results: 3.21 children were referred to the CDT per 1000 per annum. The number of referrals remained stable at a mean of 52.75 per year. The mean age of referral is 2.71, and the male to female ratio increased from 0.92 to 3.17. Consultant paediatricians and speech and language therapists refer most of the cases (30.21% and 25.53% respectively) and their number of referrals is increasing steadily. Others are mainly from health visitors and physiotherapists, and some were from parents, teachers, and social workers. In terms of diagnosis, 40.21% children had social and communication difficulties, 17.45% had global developmental delay, 15.53% with other medical disorders, 13.83% had isolated speech and language delay, and 7.87% were diagnosed with cerebral palsy. There has been a vast increase in the number of children with social and communication difficulties, rising from 23% in 2004 to 48% in 2013. There is a downward trend of children with global developmental delay and other medical causes. The number of children referred with a diagnosis of cerebral palsy remained stable. Though the referral rate remained stable, the mix of patients referred has changed, highlighting that, contrary to popular belief, CDC's treat more children with behavioural problems than medical problems. Increased awareness of such problems may be one of the reasons for this.